Exploring the Role of Multiple Representation Strategies in Social Studies Learning Outcomes Among Secondary School Students in Nigeria - Shekoni, Lateef; Sanni, Mufutau Olayiwola; Shittu, Hafees Adewale; Jimoh, Akinola Saliu; Olukoya, Tajudeen (Asian Journal of Assessment in Teaching and Learning, 2024)
The study investigates the effectiveness of a multiple representation strategy in social studies instruction on learning outcomes in Lagos State junior secondary schools. One hundred and twenty students in JSS II intact classes were used as the sample. The study employed a quasi-experimental research design with a 2x1x1 factorial matrix. The participants were drawn from the Oshodi-Isolo zone in Education District VI. Sixty students were taught using the Multiple Representation Strategy, and sixty students were taught using the conventional method. Four research questions were raised and four null hypotheses were formulated to guide the study. The Social Studies Achievement Test was used to collect data for the study. Data collected were analyzed with mean, standard deviation, and analysis of covariance (ANCOVA) at a 0.05 significance level. Findings revealed that students treated with Multiple Representation Strategy performed academically well the F-value 7.77(2, 145) is significant at 0.05, and that student’s attitude and gender is not a factor in using MRS in Social Studies class which shows that [F (2, 145) =1.740 and 1.00 (1, 145)] respectively is not significant at 0.05. The study concluded that MRS was effective in enhancing efficient learning outcomes in Social Studies. The study recommends that large-scale further application of the therapy should be employed generally at Lagos State junior secondary schools.